Mulheres camponesas e suas práticas agroecológicas: embates socioeconômicos e socioambientais na Colônia Treze, Lagarto, SE - Silva, Delmira Santos da Conceição (2023)
Peasant farming has played relevant historical, social, political and economic roles in food production, as well as in possibly ensuring food safety for Brazil and around the world. Nevertheless, peasant farming is yet to receive its deserved acknowledgement. Its current legal rights result from the struggle and confrontation of peasant farmers. In this context are female peasant farmers who, besides being involved with production and sales, must still fight for their social and agricultural rights and for the recognition of their protagonism, especially in regard to socioeconomic and socioenvironmental aspects. The object of study for the present thesis was the agroecological practices that have been developed by female peasant farmers from the village of Colônia Treze located in the state of Sergipe, Brazil. Our main goal was to understand the socioeconomic and socioenvironmental battles of female peasant farmers and the adoption (or non-adoption) of Buen-Vivir principles for their social and spatial development. The methodological procedures used were a qualitative approach to the peasant farmers’ oral history and phenomenological trajectory (in order to understand and systematize the agroecological relations of Buen-Vivir), visits to the empiric field, field journals, a semi-structured script for interviews, photographs, informal conversations and recordings. Such procedures have given basis to the creation of a documentary and to reflections upon the agroecological practices developed by female farmers in the village of Colônia Treze. The results indicate that the female farmers’ agroecological practices/experiences are partially in agreement with the theoretical aspects of Buen-Vivir. Such association is even closer when it comes to agroecological practices due to the fact that they relate to ancestral knowledge about the Earth that has been transmitted through generations, which promote preservation of both the environment and their production space. On the other hand, these elements distance themselves when there are socioeconomic questions involved because in the current scenario agroecological products are not valued as they should be. The present thesis has therefore shed light on the potential for the continuity of studies that may widen views and meanings related to agroecological practices. Moreover, this thesis reaffirms the importance of growing healthier crops as well as improving and creating public policies for the socioeconomic and socioenvironmental context of female peasant farmers.